2011
DOI: 10.3390/molecules16065079
|View full text |Cite
|
Sign up to set email alerts
|

Nematocidal Flavone-C-Glycosides against the Root-Knot Nematode (Meloidogyne incognita) from Arisaema erubescens Tubers

Abstract: A screening of several Chinese medicinal herbs for nematicidal properties showed that Arisaema erubescens (Wall.) Schott tubers possessed significant nematicidal activity against the root-knot nematode (Meloidogyne incognita). From the ethanol extract, two nematicidal flavone-C-glycosides were isolated by bioassay-guided fractionation. The compounds were identified as schaftoside and isoschaftoside on the basis of their phytochemical and spectral data. Schaftoside and isoschaftoside possessed strong nematicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…The flavone-C-glycoside, lantanoside, exhibited 90% mortality within 24 h at a concentration of 1% against M. incognita (Chitwood, 2002). Two glycosides (schaftoside and isoschaftoside) isolated from ethanolic extracts of tubers of Arisaema erubescensi possessed strong nematicidal activity against M. incognita (Du et al, 2011). The results of the present in vitro study were further strengthened by complementary data obtained from in planta experiments, where the application of root and stem extracts significantly decreased the parameters of nematode parasitism (number of galls, galling index, egg masses g )1 , eggs g…”
Section: Discussionmentioning
confidence: 99%
“…The flavone-C-glycoside, lantanoside, exhibited 90% mortality within 24 h at a concentration of 1% against M. incognita (Chitwood, 2002). Two glycosides (schaftoside and isoschaftoside) isolated from ethanolic extracts of tubers of Arisaema erubescensi possessed strong nematicidal activity against M. incognita (Du et al, 2011). The results of the present in vitro study were further strengthened by complementary data obtained from in planta experiments, where the application of root and stem extracts significantly decreased the parameters of nematode parasitism (number of galls, galling index, egg masses g )1 , eggs g…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mutant lines (Jones et al 2007) showed that flavonoids are definitely produced as part of the defense response to nematode infection but are unlikely to be an integral component of the mechanisms used by nematodes to induce feeding sites. Recently, Du et al (2011) isolated and identified two flavonones-C-glycosides, schaftoside and isoschaftoside, from the extract of Arisaema erubescens (Wall.) with strong nematicidal activity against the root-knot nematode Meloidogyne incognita.…”
Section: Impact On Soil Macrofaunamentioning
confidence: 99%
“…Many plant constituents and metabolites including essential oils have been investigated for activity against plant-parasitic nematodes [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%